Letter (copy) : Appeal - Tewson, Vincent
034-0070-001 Secretary's. HVT/FC/598. Mrs. Charlotte Haldane, Hon. Secretary, The International Brigade National Memorial Fund, 1, Litchfield Street, Charing Cross, W.C.2. 5th July, 1939. Dear Mrs. Haldane, APPEAL. Mr. Hallsworth, on his return from Geneva, has received your letter of the 23rd June in regard to the above matter and has asked me to point out that he finds some difficulty during his year of office in signing appeals or other documents in his personal capacity as it is inferred, during his Chairmanship, that he is signing in his capacity as Chairman. He has now left London for his office in Manchester and has asked me if I would explain the position to you and say that in view of the position outlined above he feels that he cannot append his signature to any document of the description you forward without consultation with his colleagues on the General Council. Yours sincerely, Assistant Secretary. 292/946/34/70